Why we should talk less about information management and more about knowledge management - Alí²s-Moner, Adela (Anuario ThinkEPI, 2012)
This article begins by establishing the differences between information management (focus on access to content and, therefore, technology) and knowledge management (focus on adding value to content and, therefore, corporate culture) and then addresses the problems in the practical implementation of the latter in organizations, even though its use is able to provide knowledge to organizations that enables them to make decisions under the best conditions.